THE ROLE OF READING IN PROMOTION LIFELONG LEARNING AND INTELLECTUAL GROWTH - Xo’jayeva Xayriniso; Abdurahmonov T (TADQIQOTLAR.UZ, 2024)
Abstract:  Reading  plays  a  pivotal  role  in  promoting  lifelong  learning  and intellectual  growth,  offering  individuals  the  tools  to  continuously  expand  their knowledge,  enhance  cognitive  abilities,  and  engage  with  the  world  around  them. Through regular reading, individuals can develop critical thinking, analytical skills, and a broader vocabulary, all of which contribute to their intellectual and professional development. Reading also fosters empathy, creativity, and emotional intelligence by exposing readers to diverse perspectives and experiences. Furthermore, it stimulates mental health by reducing stress and supporting cognitive longevity. By cultivating a growth mindset, reading encourages individuals to embrace learning as an ongoing process, making it a foundational activity for lifelong personal and intellectual growth. This  article  highlights  the  multifaceted  ways  in  which  reading  contributes  to  the development of a well-rounded, informed, and adaptable individual.